(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Obesity has become a major worldwide health problem and therefore, the associated morbidity, mortality and both medical and economical costs are expected to increase as well. Obesity increases cardiovascular risk via risk factors such as triglycerides (TG), high LDL cholesterol, low HDL cholesterol, elevated plasma glucose and insulin concentrations. Objective: To investigate the effect of metformin and betahistine along with lifestyle change on lipid profile in obese women in Iraq. Methods: This study was carried out on 78 female patients with age range of 18-50 years who were allocated into three groups: Group 1: treated with oral metformin 850 mg twice daily with lifestyle change for 12 weeks. Group 2: treated with betahistine 32 mg 3 times daily with lifestyle change for 12 weeks. Group 3: treated with placebo 500 mg twice daily with lifestyle change for 12 weeks to serve as control. Complete history was taken, in addition to clinical examination to meet inclusion criteria. Serum transaminases (ALT+AST) and estimated glomerular filtration rate (GFR) were estimated at baseline to exclude hepatic or renal abnormalities. Results: Each metformin and betahistine, along with lifestyle intervention highly significantly reduced total cholesterol level, LDL-C level, TG and VLDL level, and increased plasma level of HDL after 12 weeks in obese women with disturbed lipid profile compared to pre-treatment values, and the changes elicited by metformin and betahistine (plus lifestyle change) were highly significant compared to placebo (lifestyle change alone). Conclusion: The results obtained in this study clearly demonstrated the beneficial effect of using metformin or betahistine to obese women with dyslipidemia and confirmed the role of pharmacotherapy in targeting the lipid metabolism changes accompanying obesity. Keywords: Obesity, dyslipidemia, lifestyle change, betahistine, metformin DOI: 10.22578/IJMS.14.4.5